Short‐term and long‐term outcomes of oesophagogastric surgery for cancer in obese and normal weight patients. Issue 3 (18th December 2019) - Glatz, Torben; Kulemann, Birte; Kuvendjiska, Jasmina; Fichtner‐Feigl, Stefan; Hoeppner, Jens
Abstract: Background: Obesity is generally considered to be associated with worse surgical outcome and impaired oncological prognosis. The impact of pre‐therapeutic body mass index (BMI) in patients with oesophagogastric cancer on the surgical outcome is controversially discussed. Methods: We retrospectively examined 730 patients who had undergone curative treatment for oesophagogastric cancer at the Medical Center of the University of Freiburg (1996–2015). Patients were divided in groups according to pre‐therapeutic BMI (underweight (UW): <18.5 kg/m 2 ; normal weight (NW): 18.5–25 kg/m 2 ; overweight (OW): 25–30 kg/m 2 ; and obese (OB): >30 kg/m 2 ). Results: Median BMI was 24.7 kg/m 2 . Forty‐two patients were UW, 337 NW, 263 OW and 84 OB. No significant differences between the groups (UW/NW/OW/OB) in operating time, hospital stay, perioperative complication rate and in‐hospital mortality were found. Pre‐therapeutic BMI was significantly associated with 5‐year survival (UW: 22%, NW: 37%, OW: 51%, OB: 50%, P  < 0.001). Multivariate analysis identified UW/NW (BMI <25 kg/m 2 ) as an independent risk factor for poor survival (relative risk 1.38, P = 0.001) among high American Society of Anesthesiologists score, old age, positive resection margin and high cancer stage according to the Union Internationale Contre le Cancer (UICC). Conclusion: In oesophagogastric cancer, OW and OB patients can be treated surgically without impaired perioperative outcome and expect improved long‐term survival compared to patients with a BMI <25 kg/m 2 . Abstract : The impact of pre‐therapeutic body mass index (BMI) in patients with oesophagogastric cancer on perioperative outcome and long‐term survival is controversely discussed. We retrospectively examined 730 patients who had undergone curative treatment for oesophagogastric cancer at the Medical Center of the University Freiburg between 1996 and 2015. Our study shows that overweight and obese patients with a BMI <35 kg/m 2 can be treated without impaired perioperative outcome and expect improved long‐term survival compared to patients with a BMI <25 kg/m 2 .